Pengembangan Literasi Pancasila Pada Pembelajaran Materi Norma dalam Kehidupan Masyarakat - Mahmud, Mahmud; Awaliyah, Siti; Suhartono, Edi (Universitas Negeri Malang, 2024)
This study aims to develop and test the feasibility, practicality, and effectiveness of Pancasila literacy in Pancasila and Citizenship Education learning. This study used the Borg and Ball research and development method. The resulting product is Pancasila literacy in Pancasila and Citizenship Education learning on norms in community life that are feasible, practical, and effective. The product feasibility test is based on the results of Pancasila literacy expert validation of 91.76 percent, material validation of 94.12 percent, and learning expert validation of 92.31 percent. The practicality test is based on the results of teacher responses to small group trials of 91.67 percent and large group trials of the first meeting of 91.67 percent and the second meeting of 95.00 percent. The level of practicality is also obtained from the results of student response questionnaires in small group trials of 90.21 percent and large group trials of the first meeting of 90.21 percent and the second meeting of 91.18 percent. The effectiveness test is based on the results of the first meeting survey of 87.14 percent increasing to 91.69 percent, while in the second meeting of 91.69 percent increasing to 93.23 percent. These results indicate that there has been an increase in Pancasila literacy from students.